Objectively-assessed neighbourhood destination accessibility and physical activity in adults from 10 countries: An analysis of moderators and perceptions as mediators - Cerin, Ester; Conway, Terry L; Adams, Marc A; Barnett, Anthony; Cain, Kelli L; Owen, Neville; Christiansen, Lars B; van Dyck, Delfien; Mitáš, Josef; Sarmiento, Olga L; Davey, Rachel C; Reis, Rodrigo; et al. (Social science & medicine (1982), 2018)
RATIONALE: Residents of neighbourhoods with high destination accessibility (higher population density, more-interconnected streets, and better access to services, public transport and parks) are more physically active. Evidence on the factors that underlie these associations is sparse and inconsistent. OBJECTIVE: We examined (1) five socio-demographic and four non-destination perceived neighbourhood attributes as moderators of the relationship between objectively-assessed destination accessibility and moderate-to-vigorous physical activity (MVPA); (2) perceived indicators of destination accessibility as mediators of those relationships; and, (3) the generalizability of findings across 14 cities. METHODS: Data were from the International Physical Activity and Environment Network (IPEN) Adult study (N = 6822), which provided comparable objective and perceived environmental variables and accelerometer-based MVPA from 14 cities across 10 countries. Mediation and mediation moderation analyses were performed. RESULTS: Objective net residential density, public transport density, and number of parks in the neighbourhood were consistently associated with MVPA across all examined socio-demographic groups and non-destination perceived neighbourhood characteristics. However, only the association between number of parks and MVPA was mediated by its conceptually-comparable perceived indicator. While the associations of objective intersection density and land use mix with MVPA were moderated by both gender and perceived pedestrian infrastructure/safety, only the latter moderating effects were mediated by the conceptually-comparable perceived indicators. Perceived neighbourhood safety and/or aesthetics moderated the associations of objective ratio of retail/civic land to total area and distance to nearest transport stop with MVPA. These associations were not mediated by the conceptually-comparable perceived indicators. CONCLUSION: Densely populated neighbourhoods with access to public transport and parks have the potential to significantly and equitably contribute to adults' MVPA on a global scale. Perceived neighbourhood aesthetics, pedestrian-friendliness and safety can magnify the positive effects of mixed-use neighbourhoods on residents' MVPA by interacting with the perceived ease of access to a variety of destinations.
Keywords: životní prostředí - projekt; dospělí; China; Epidemiologic Studies; Cross-Sectional Studies; Brazílie; Denmark; Čína; Dánsko; veřejné parky; Humans; lidé středního věku; Middle Aged; Physical activity; Perception; Mediated moderation; Environment Design; Health Services Accessibility; Exercise; Kolumbie; Czech Republic; percepce; Belgium; Nový Zéland; Spojené státy americké; charakteristiky bydlení; mužské pohlaví; Residence Characteristics; Česká republika; dostupnost zdravotnických služeb; Transportation; United Kingdom; Geographic information systems; Sociodemographic characteristics; Adult; Walkability; průřezové studie; cvičení; Parks, Recreational; Perceived neighbourhood attributes; Public transport; Mexiko; ženské pohlaví; Colombia; doprava; Brazil; Spojené království; United States; lidé; epidemiologické studie; Aged; Mexico; Parks; senioři; Male; New Zealand; Belgie; Female